Orchestration mechanism for VNF hardware acceleration resources in SDN/NFV architecture - Tong DUAN; Julong LAN; Yuxiang HU; Hongwei FAN (Tongxin xuebao)
The hardware acceleration mechanism for VNF (virtual network function) is recently a hot research topic in SDN/NFV architecture because of the low processing performance of VNF.Once hardware acceleration resources have been plugged into the network,how to optimally mange and orchestrate these resources under service requirements remains a question to be solved.Firstly,a unified management architecture based on separated control for hardware acceleration resources was proposed.Then,traditional network topology together with hardware acceleration resources were modeled into a unified network model and then the hardware acceleration resource orchestration problem was transferred into a multi-objective linear programming problem.Finally,a hardware-accelerator-card-prior’ heuristic algorithm was designed.Experimental results show that compared with existing methods,the proposed orchestration mechanism can efficiently manage hardware acceleration resources and reduce the processing latency by 30%.